MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA LAPBOOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Sekar Kinasih, Ontya; Virdinarti Putra, Lisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine and analyze the effect of the Jigsaw cooperative learning model assisted by lapbook media on students' problem-solving skills. This research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The population of this study consisted of all fifth-grade students of SDN Langensari 04, Semarang Regency. The sample included an experimental class that received instruction through the Jigsaw cooperative learning model assisted by lapbook media and a control class that received conventional learning. Data were collected through problem-solving skill tests administered before (pretest) and after (posttest) the treatment. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing. The results showed that there was a significant difference in problem-solving skills between students in the experimental class and those in the control class. Students who learned through the Jigsaw cooperative learning model assisted by lapbook media demonstrated a higher improvement in problem-solving skills compared to students who experienced conventional learning. Therefore, it can be concluded that the Jigsaw cooperative learning model assisted by lapbook media has a significant effect on students' problem-solving skills. This learning model can serve as an effective alternative for enhancing students' problem-solving abilities through active participation in the learning process.